Admiration and Motivation. (April 2019) - Archer, Alfred
What is the motivational profile of admiration? In this article, I will investigate what form of connection between admiration and motivation there may be good reason to accept. A number of philosophers have advocated a connection between admiration and motivation to emulate. I will start by examining this view and will then present objections to it. I will then suggest an expanded account of the connection between admiration and motivation, according to which, admiration involves motivation to promote the value that is judged to be present in the object of admiration. Finally, I will examine the implications of this account for the use of admiration in education.